The need to escape: Carceral entrapments and fugitive manoeuvres amidst London’s vicious housing circle - Toni Adscheid (Radical Housing Journal, 2024)
The contemporary housing system in England entraps temporary tenants in ongoing movement between different types of insecure, unaffordable, overcrowded and poorly maintained accommodations. Engaging with carceral geography scholarship and Black fugitive thinking, I argue that a legalised system of cacerality entraps temporary tenants in recurrent movement, thus reproducing a ‘vicious housing circle’. However, I also stress how temporary tenants and housing campaigners maintain spaces of care that hold open possibilities to escape the entrapment in movement. Grounded in my ethnographic research with the Focus E15 housing campaign, in the East London borough of Newham, I highlight the struggle of the campaign as urgent call for urban geographic scholarship to foreground and challenge the carcerality of London’s ‘vicious housing circle’. Based on the struggle of the Focus E15 campaign I offer an extension to debates around the ‘right to stay put’, considering a fugitive politics articulated around the ‘need to escape’.